1999
DOI: 10.1098/rspb.1999.0651
|View full text |Cite
|
Sign up to set email alerts
|

Virulence evolution in a virus obeys a trade off

Abstract: The evolution of virulence was studied in a virus subjected to alternating episodes of vertical and horizontal transmission. Bacteriophage f1 was used as the parasite because it establishes a debilitating but non-fatal infection that can be transmitted vertically (from a host to its progeny) as well as horizontally (infection of new hosts). Horizontal transmission was required of all phage at specific intervals, but was prevented otherwise. Each episode of horizontal transmission was followed by an interval of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
182
2
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(192 citation statements)
references
References 33 publications
(46 reference statements)
6
182
2
2
Order By: Relevance
“…2 E-mail address: ingnang@albany.edu host resources also can increase the host's mortality rate, decreasing the expected duration of the infectious period (similar arguments apply to immune-driven recovery). Therefore, excessive virulence might decrease the total number of infections transmitted per infection, so that a trade-off between intensity and duration of disease transmission induces selection for intermediate virulence (Ebert, 1994;Lipsitch and Moxon, 1997;Messenger et al, 1999;van Baalen and Sabelis, 1995;Gandon et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…2 E-mail address: ingnang@albany.edu host resources also can increase the host's mortality rate, decreasing the expected duration of the infectious period (similar arguments apply to immune-driven recovery). Therefore, excessive virulence might decrease the total number of infections transmitted per infection, so that a trade-off between intensity and duration of disease transmission induces selection for intermediate virulence (Ebert, 1994;Lipsitch and Moxon, 1997;Messenger et al, 1999;van Baalen and Sabelis, 1995;Gandon et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It is classically admitted that evolution tends to select parasite strains of the highest R 0 in homogeneous populations under a trade-off between transmissibility and virulence (Ewald 1994;Frank 1996;Messenger et al 1999;Ebert & Bull 2003). Surprisingly, the fact that the risk of stochastic fade-out may represent a strong selection pressure for parasites has been less studied, and it is only very recently that the concept of stochastic selection pressure for parasites has been developed (Andre & Hochberg 2005;Read & Keeling 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Avoiding either of these factors might provide the evolutionary pressure for tra repression. Furthermore, increased horizontal transfer might reduce vertical transmission by slowing host growth; such tradeoffs have been predicted and observed for diverse parasites (Bull et al, 1991;Kover et al, 1997;Kover and Clay, 1998;Messenger et al, 1999;Dahlberg and Chao, 2003;Jensen et al, 2006). Plasmids display a tradeoff between conjugation rate and vertical transfer (Turner et al, 1998;Turner, 2004), and have been shown to evolve reduced cost to the host at the expense of horizontal transfer when the environment limits conjugative spread (Dahlberg and Chao, 2003).…”
Section: Introductionmentioning
confidence: 99%